Práticas de comunicação em instituições públicas de ensino superior: as estratégias da UFPE para as mídias sociais em tempos de crise. - Barbosa, Sueli Marcia Pereira (2020)
The changes brought about by information and communication technologies have changed communication practices. Now networked, through the internet, media and digital social networks have become essential elements for companies and institutions to reach a larger audience and, therefore, their objectives and goals. Among the recent practices, one of them worried us: how do Higher Education Institutions deal with their information and with their public on social networks, especially in times of crisis? Thinking about the insertion of these institutions in these environments, we opted for a case study, having as locus the Federal University of Pernambuco (UFPE). Therefore, we have as a general objective to analyze the communication practices used by the University, in its social networks, starting from the guidelines of the University's institutional plans aligned to the public interest. For this purpose, we seek to describe the strategic communication policies and practices adopted by the Institution in the management of social media, identifying the information provided by UFPE with potential for public interest and analyzing the activities of interactivity and users engagement, in the main networks official social media of the institution (Facebook, Twitter, Instagram). With an exploratory bias and a qualitative approach, the analyzed corpus was constituted by posts in the official pages of the institution, namely UFPE Oficial and Ascom UFPE, with clipping of events considered of public interest, which involve reducing or cutting funds in universities, in two periods distinct. The theoretical foundations were extracted from the works of Castells (1999, 2005, 2009, 2017); Harvey (2003); Kumar (2006) and Sodré (2002) who address communication and technologies; Maximimino (2000); Duarte (2009); Bueno (2005, 2014a, 2014b, 2015) and Novelli (2006) were inspiring for studies of communication, and management and public administration; Recuero (2009); Lemon and Verhoef (2016); Pine and Gilmore (1998) and Mergel (2013, 2013b) brought references to the issues pertinent to engagement on social networks. The study analyzed the institutional development plans, resolutions and policies adopted by UFPE, the guidelines of the Communication Secretariat of the Presidency of the Republic and their implications for federal public institutions, as well as the opinions of the Federal Court of Accounts (TCU). As a result of the analysis, in addition to the dissertation itself, we also present a guide that aims to guide practices for the social networks of UFPE sectors that deal with information and communication on digital platforms.